An improved beetle antennae search algorithm with Lévy flight and its application in micro-laser assisted turning. (October 2022) - He, Wenbin; Lin, Chuangting; Wu, Tung-An; Tang, Xian; Chen, Xiao; Xu, Jianfeng
Highlights: An improved beetle antennae search algorithm (IBAS) is proposed. Fifteen benchmark functions and four engineering problems are used for validation. A solution is developed for laser energy prediction in micro-laser assisted turning. The outcomes suggest a better performance of IBAS relative to other techniques. Abstract: The beetle antennae search (BAS) algorithm is a single-solution metaheuristic optimizer that imitates the foraging behavior of beetles. Due to its easy implementation and fast convergence, it has been applied in various engineering fields. To enhance the local search ability and preclude the blindness of position updates performed in BAS, an improved beetle antennae search algorithm with Lévy flight (IBAS) is proposed in this paper. Additionally, to further enhance the algorithm performance, the features of inertia, normalization, and elitist selection are adopted into this proposed hybrid algorithm. In a comparison with other algorithms based on 15 well-known benchmark functions and 4 classic engineering problems, IBAS maintains good performance under the premise of a trade-off between efficacy and efficiency. The detailed results suggest that the improvements adapted in IBAS alleviate the shortcomings of BAS. In addition, a real-world engineering problem, laser energy prediction in micro-laser assisted turning, is used to further validate the potential of the proposed algorithm for industrial applications. The results indicate the feasibility of the new solution based on the IBAS algorithm. Two further applications of IBAS in the reconstruction of the temperature field and online laser energy detection are also discussed.